GRAPHICAL ANALYSIS OF THE ORTHOPYROXENE-PIGEONITE-AUGITE-PLAGIOCLASE EQUILIBRIUM AT LIQUIDUS TEMPERATURES AND LOW PRESSURE - Latypov R.M.; Dubrovskii M.I.; Alapieti T.T. (My University, 2001)
There are both natural and experimental observations of the coexistence of three pyroxenes—orthopyroxene (Opx) + pigeonite (Pig) + augite (Aug)—with plagioclase (Pl). Commonly, the assemblage occurs as an intermediate product in the following fractionation trend of a mafic magma: Opx + Aug + Pl → Opx + Aug + Pig + Pl → Aug + Pig + Pl. To clarify the phase-equilibria constraints on the existence of this mineral assemblage, we have graphically analyzed the change in topology of an isobaric–isoplethic section, Ol–Aug–Pl–Qtz [with fe = 25–50%, where fe = Fe/(Fe + Mg), and An = 50%], arising from an increase in the fe-value of silicate liquid. The analysis shows that the stability field of the mineral assemblage Opx + Aug + Pig + Pl is restricted, and can onlycrystallize in the interval between two invariant points—T41 (Ol + Opx + Pig + Aug + Pl + L) and T42 (Qtz + Opx + Pig + Aug + Pl + L)—that emerge successively during expansion of a liquidus volume of pigeonite within the isobaric–isoplethic section Ol–Aug–Pl–Qtz. At fe-values lower than T41, the 3-pyroxene assemblage cannot exist due to the absence of a contact surface between the primary volumes of plagioclase and pigeonite. At fe-values greater than T42, the assemblage is unstable due to separation of the primary volumes of orthopyroxene and augite.